Hybrid Repair of Aortic Arch Aneurysms in Same Session - Yilik, Levent; Gokalp, Orhan; Yurekli, Ismail; Bayrak, Serdar; Gunes, Tevfik; Karakas, Nihan; Ozsoyler, Ibrahim; Gurbuz, Ali (The Thoracic and Cardiovascular Surgeon, 2012)
Background Management of thoracic aorta aneurysms—especially the ones including aortic arch—is highly complicated. Isolated or nonisolated aortic arch aneurysms can be repaired by hybrid procedure especially in patients with comorbidities as well as by conventional open methods.Methods Eleven patients who underwent total arch debranching and endovascular stent implantation on antegrade route in the same session between November 2006 and October 2009 were retrospectively evaluated using clinical and perioperative criteria.Results The mean age was 65 ± 6.2 and nine of the patients were male. Primary technical success rate was 100%. Mortality, stroke, or transient paraplegia/paraparesia was not seen during in-hospital follow-up. Average follow-up period was 36 ± 13 months and no late-term aortic pathology was seen. In only one of the patients, endovascular reintervention was required for type 1B endoleak. No mortality or neurological pathology was seen in long-term postoperative follow-up.Conclusion Hybrid procedures could be performed safely with lower complication and higher success rates in the same session via antegrade route and zone 0 graft deployment for high-risk cases with isolated or nonisolated aortic arch aneurysms.
Keywords: aorta/aortic; artery/arteries (includes all peripheral arteries); aneurysm